KEKHAWATIRAN PARA KAUM MUDA DALAM MENGEMUKAKAN PENDAPAT DAN PENCARIAN JATI DIRI - Zebua, Faozanolo (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This article aims to understand why young people often hesitate to express or express their opinions, what their anxieties and worries are, or whether they have their own reasons for doing so. This article, which discusses all of these aspects, will explore several theoretical studies, such as sociology and Pancasila, and even discuss the psychology of young people. The discussion on why all of this can happen to young people is due to internal and external factors from within themselves and their environment. The conclusion from these concerns about expressing opinions and searching for identity is that it is hoped that young people will want to broaden their insight and knowledge about various things and aspects, and respect and honor the opinions of others, whether older, their peers, or younger. This attitude of mutual respect for the opinions and aspirations of everyone will build a better place to develop than before. Furthermore, the presence of family, friends, and society as a whole is also very necessary to provide the necessary support to young people. Providing a safe and welcoming space for them to voice their opinions and explore their identities will go a long way in alleviating their anxieties. With the right support, young people will feel more confident and motivated to pursue their aspirations, express their opinions assertively, and ultimately discover their true selves.